Grassmannian and bosonic Thirring models with jump defects - Aguirre, A. R. [UNESP]; Gomes, J. F. [UNESP]; Ymai, L. H.; Zimerman, Abraham Hirsz [UNESP] (Springer, 2011)
In this paper we discuss the Lax formulation of the Grassmannian and Bosonic Thirring models in the presence of jump defects. For the Grassmannian case, the defect is described by Backlund transformation which is responsible for preserving the integrability of the model. We then propose an extension of the Backlund transformation for the Bosonic Thirring model which is verified by some Backlund transitions like vacuum-one soliton, one soliton-one soliton, one soliton-two solitons and two solitons-two solitons. The Lax formulation within the space split by the defect leads to the integrability of Bosonic Thirring model with jump defects.
Keywords: Solitons Monopoles and Instantons; Integrable Field Theories